Optimalisasi Peran Kader Kesehatan Melalui Pelatihan Self-Care Management Hipertensi: Optimizing the Role of Health Caders Through Hypertension Selft Care Management Training - Wirawan, Alfonsius Ade; Fernandez, Gratsia Victoria; Kambey, Stefan Andrew Glorious Pelealu (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The high prevalence of hypertension in Indonesia shows the need for efforts to increase public awareness in managing hypertension as a preventive measure for hypertension complications. One of the efforts made is hypertension self-care management. Objective: to increase the knowledge of health cadres through hypertension self-care management training. This activity was divided into 5 stages: location survey, problem identification, preparation of educational media, training, and evaluation, all carried out through pre- and post-test measurements. Twenty-five health cadres attended the activity. They were enthusiastic about participating in the activity. The average pre-test score was 47.2, and the average post-test score of the health cadres was 77.6. This shows that there was an increase in pre-post test knowledge of 30.4, with a p-value of 0.00 (<0.05). Hypertension self-care management training has a positive impact on health cadres in increasing their knowledge. Hypertension self-care management is very important for patients and families to prevent complications of hypertension.